Methodology of Spatial Data Acquisition and Development of High-Definition Map for Autonomous Vehicles - Case Study from Wrocław, Poland - Siejek, Martyna; Kasza, Damian; Wajs, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Autonomous drive systems are a dynamically developed sector of the automotive industry. The key problem in such technological solutions is to provide a reliable navigation system, which is typically based on high-definition (HD) maps supporting the identification of the position of a maneuvering vehicle. HD maps should include possibly up-to-date and detailed information on traffic lanes and on the traffic rules and regulations on such lanes. An effective development of an HD map should be based on the geodetic measurement methods, which ensure efficient and accurate acquisition of spatial data.
Keywords: mobile laser scanning; HD map; autonomous cars; autonomous driving; 3D modeling